Estrategias de viralización de las noticias y sus efectos: Caso Teleamazonas 2021 - Montes Chila, Shirley Vanessa (2022)
This case study focuses on analyzing the problem of the viralization of news and its effects in the case of Teleamazonas. With the arrival of the internet and social networks, they have caused a change in traditional media such as: radio, television, the newspaper, thus allowing them to create digital platforms to keep in constant changes with technology, due to this many people reach the information that is published to achieve the respective content viralizations. The dissemination of false news on social networks such as: Facebook, Twitter, Instagram also causes viralization and negative effects due to misinformation, the lack of ethics in uploading misreported and detailed information causes conflicts between users. The effect of viralization of news is caused by the interest generated in users, who share the information massively and contribute to its spread through the medium, producing a chain that increases the visibility and impact of the content uploaded.